“It was a Hard Life”:Class and Gender in the Work and Family Rhythms of a Railway Town, 1920‑1950 - Rosenfeld, Mark (Historical Papers / Communications historiques, 1988)
AbstractMost social histories of the working class have focussed on women's or men's experiencealone. However, while studies of working-class women have often been sensitive to theway in which class and gender relationships are constructed and reconstructedsimultaneously, histories of working-class men have been largely gender-blind. In anattempt to provide a more comprehensive understanding of gender-based divisions inthe working-class experience this study examines the relationship between male andfemale work worlds in the railway ward of Barrie, Ontario between 1920 and 1950.Based primarily on oral history, this paper argues that the class and genderconditions and relations of the period set limits to what was available and possible for themen and women of the railway ward. In most families, husbands were breadwinners andwives were full-time homemakers. This pattern was the response of railroad families tothe constraints created by the gender division of wage work, railway labour rhythms, theprevailing conditions of reproductive labour, and the ideology of patriarchy. None theless, railroaders and their wives also made choices within the limitations of their lives.These choices had different implications for the men and women of the community.The strategies men and women adopted for survival and well-being also began tochange over the period, both altering as well as being changed by the constraints theyfaced. As conditions changed, concepts of masculinity and femininity which informedtheir strategies began to shift — but not dramatically. The experience of the railwaycommunity revealed that the construction of gender identities was a complex andcontradictory process. Indeed, the historical literature on the social construction ofgender has really only began to grapple with the many dimensions which comprised thatprocess.